ANALISIS DAMPAK WISATA MANGROVE TERHADAP PENDAPATAN MASYARAKAT KAMPUNG POMAKO DI WILAYAH DISTRIK MIMIKA TIMUR KABUPATEN MIMIKA - Baiq Rohmini; Nely Salupadang (ADISAM PUBLISHER, 2024)
The study aims to determine the impact to before and after mangrove tourism in Pomako Village, east Mimika District, Mimika Regency. The method used is a comparative method, research data were collected using a paired sample t-test. The results of the study indicate that there is a diflerence in income before an after mangrove tourism